Meeting The Food and Nutritional Needs of Street Children in Kupang City - Mega, Amanda Pusparini; Romeo, Petrus; Ndoen, Enjelita Mariance (Universitas Nusa Cendana, 2023)
Kupang City ranked fourth with the highest number of street children in NTT Province in 2016-2017. Street life makes street children a marginalized group who are very vulnerable to various issues, including those related to nutrition. This research aims to determine the problem of meeting the food and nutritional needs of the street child community in Kupang City. The research was qualitative with a phenomenological approach. The research informants were seven street children selected by purposive sampling technique. Data were collected through active participant observation and in-depth interviews with interview guides, notebooks, voice recorders, tripods, and cell phone cameras as research instruments. Data were processed qualitatively from transcripts, observations, and field notes. The research identified several problems with the informants' food and nutritional needs, including limited menu/unbalanced diet, low quality of food, consumption of unhealthy snacks, limited consumption of drinking water, irregular meal times, and unpleasant experiences regarding food donation.